Comparison of Swimmers’ Health-Related Fitness Parameters in General and Special Preparation Periods - İlhan Odabaş; Benil Kıstak Altan (Research in Sport Education and Sciences)
This study aimed to compare the health-related fitness parameters of swimmers in the general and special preparation periods. Thirty-six swimmers participated voluntarily. Before and after general and after special preparation, measurements of the swimmers’ endurance, strength, flexibility, body composition, and respiratory parameters were taken. The pre and post-tests were conducted at two-month intervals before and after general preparation, as well as after special preparation. After the initial measurements, swimmers undertook the general training program for eight weeks, followed by repeated measurements. Following this, speed-based special training was continued for eight weeks, after which the measurements were repeated. Data was analyzed using the SPSS 24.0. As the data displayed normal distribution, we performed a repeated measures variance analysis to compare all parameters among swimmers across three different periods. Significant differences were found in the body composition (lean body weight pre-general 36.79±3.97kg post-general 37.25±3.96kg post-special 37.73±3.88kg), respiratory function (FVC pre-general 3.30±0.56L post-general 3.44±0.55L post-special 3.59±0.54L), flexibility (pre-general 26.00±7.74cm post-general 26.44±6.94cm post-special 27.51±7.79cm), hand grip strength (pre-general 42.35±12.58kg post-special 51.33±11.71kg), and isokinetic shoulder strength (ΔAverage power~4W ΔAverage peak torque~2Nm) (p